Continuous thermosalinograph oceanography along RV ALKOR cruise track AL618 - Michael Schlundt; David Needham; Felix H Mittermayer (PANGAEA, 2025)
Underway temperature and salinity data was collected along the cruise track with a thermosalinograph (TSG) together with a SBE38 Thermometer. Both systems worked throughout the cruise. While temperature is taken at the water inlet in about 4 m depth, salinity is estimated within the interior TSG from conductivity and interior temperature. No temperature calibration was performed. Salinity was calibrated with independent water samples taken at the water inlet. For details to all processing steps see Data Processing Report.